Where is the I(nformation) in GLAM? Education, Knowledge and Skill Requirements of Professionals Working in GLAM Sector Institutions. Issue 3 (3rd July 2019) - Kennan, Mary Anne; Lymn, Jessie
ABSTRACT: This paper presents findings of a qualitative investigation of the employer-identified knowledge and skills required of professionally trained staff in the galleries, libraries, archives and museums (GLAM) sectors. Six group interviews and six individual interviews were conducted with Directors or their representatives from GLAM institutions in major and regional cities in Australia. The interviews were analysed according to the institution type, and the knowledge and skills discussed. The findings are situated within a wider conversation about the convergence of GLAM institutions, proposing that LIS education programs may have an opportunity to adapt their current courses to meet the needs for collaborative skills and knowledge in this sector.